Generalization as a Means of Suggestion in Modern Political Discourse - Kalishchuk, Diana (East European Journal of Psycholinguistics, 2014)
The article deals with the notion of suggestion as one of the main features of modern political discourse, the processes of deletion, generalization and distortion of information, that cause non-identity between the deep informational content of the utterance and it’s represented version and therefore are used to influence the addressee, are described; language means used to realize the process of generalization are defined and analyzed, namely:  universal quantifiers, including some adverbs and pronouns; modal operators of obligation / possibility, such as modal verbs with the meaning of obligation / possibility, and other parts of speech (adjectives, adverbs, particles), semantics of which presupposes necessity or obligation of some actions; intensifiers, which modify the pragmatic meaning of the utterance and therefore intensify the impact on the addressee.ReferencesAvdeenko I. (2001). Strukturnyie i suggestivnyie svoistva verbalnykh sostavliaiushchikhreklamnogo teksta [Structural and Suggestive Verbal Components Characteristics of Advert Text].Barnaul.Bendler R., Grinder D. (1995). Ispolsuite Svoi Mozg dlia Izmeneniia [Use Your Brains toChange]. Moscow.Feis R. (1974). Modalnaia Logika [Modal Logic]. Moscow: Nauka.Girutskii A. (2010). Neirolingvistika: posobiie dla studentov vuzov [Neurolinguistics: a manualfor university students]. Minsk: Tetrasystems.Kovalevska T. (2001). Komunicatyvni Aspekty Neirolinhvistychnoho Programuvannia[Communicative Aspects of Neuro-linguistic Programming]. Odessa: Astroprint.Nickl M. (1998). Einige Entwürfe und Einträge in der neuenkommunikationswissenschaftlichenPersuasionsforschung. Beiträge zur Persuasionsforshung. Frankfurt: Peter Lang.Shcherban’ M. (2008). Semantychna Kharakterystyka Intensyfikatoriv PrahmatychnohoZnachennia: Sproba Formalisovanoho Opratsiuvannia [Semantic Characteristics of Pragmatic MeaningIntensifiers: An Attempt of Formalized Analysis]. Retrieved 14.02.2014 from eprints.zu.edu.ua/2475/1/227-230. dfStankevych Yu. (2011) Movni Sugestoheny u Tekstakh Politychnoii Reklamy [LanguageMeans of Suggestion in Political Advert Text]. PhD Thesis. Odessa.SourcesComplete Final Debate Transcript: John McCain and Barack Obama (CFD). October 15, 2008.Retrieved 14.02.2014 from: http: //latimesblogs.latimes.com/washington/2008/10/debate-transcri.htmlFull text of Barack Obama’s speech in Osawatomie, Kansas (BOS 2011). – 7 December, 2011.Retrieved 14.02.2014 from: http: //www.guardian.co.uk/world/2011/dec/07/full-text-barack-obamaspeechHillary Rodham Clinton. Remarks to the Center for Global Development (Clinton 2010).January 6, 2010. Retrieved 14.02.2014 from: http: //www.state.gov/secretary/rm/2010/01/134838.htmObama Inaugural Address. 20th January 2009 (OIA). Retrieved 10.02.2014 from: http://obamaspeeches.com/Obama U.N. speech transcript 2013 (OUNS 2013). Retrieved 10.02.2014 from: http://www.politico.com/story/2013/09/obama-un-speech-transcript-2013-97261.htmlRemarks by the President Obama and Former President Clinton on We Can’t Wait: BetterBuilding Initiative. December 02, 2011 (BBI). Retrieved 10.02.2014 from: http://www.whitehouse.gov/ the-press-office/2011/12/02/remarks-president-obama-and-former-presidentclinton-we-cant-wait-betterRemarks by the President on the American Jobs Act (AJA). November 20, 2011. Retrieved10.02.2014 from: http: //www.whitehouse.gov/the-press-office/2011/11/30/remarks-presidentamerican-jobs-actRemarks by the President on the Defense Strategic Review. January 05, 2012 (DSR). −Retrieved 10.02.2014 from: http: //www.whitehouse.gov/the-press-office/2012/01/05/remarkspresident-defense-strategic-reviewState of the Union Address (January 31, 2006). Retrieved 10.02.2014 from: http://millercenter.org/president/speeches/detail/4461State of the Union Address (February 2, 2005). George W. Bush. Retrieved 10.02.2014 from:http: //millercenter.org/president/speeches/detail/4464State of the Union Address. George W. Bush. January 23, 2007. Retrieved 10.02.2014 from:http: //millercenter.org/president/speeches/detail/4455The Second Presidential Debate. October 07, 2008. Retrieved 10.02.2014 from: http://elections.nytimes. com/2008/president/debates/ transcripts/second-presidential-debate.htmlTranscript of President Barack Obama’s Speech on the Republican Budget Plan at ASNE.April 03, 2012 (SRBP). Retrieved 10.02.2014 from: http: //www.washingtonpost.com/politics/fulltranscript-barack-obama-speech-before-newspaper-editors/2012/04/03/gIQArZ9ctS_story.html